Efecto de la adición del suero de mantequilla dulce en las características fisicoquímicas, color, reología y estabilidad proteica del yogur - Santillan Mata, Erick Alexander (2026)
Sweet buttermilk is a byproduct of dairy production that, when recovered, offers excellent potential for use in the development of new products due to its content of functional components. The objective of this research was to analyze the influence of adding sweet buttermilk on the physicochemical characteristics, viscosity, and sensory acceptance of yogurt. The research was quantitative, employing an experimental methodology. A completely randomized design with a single factor was used: 5%, 10%, and 15% buttermilk in yogurt, with three replicates for a total of three storage times (1, 8, and 15 days). pH and titratable acidity were recorded for the different treatments during the storage period. The physicochemical characteristics (density, viscosity, and protein content) of each treatment were also evaluated. In addition, a standard sensory analysis test (color, odor, flavor, texture, and overall acceptability) was conducted using a five-point hedonic scale. A total of 25 untrained panelists, all regular consumers of this type of product, participated. The results indicated that the use of buttermilk had a significant impact on acidity and pH, with acidity increasing and pH decreasing as storage progressed. The 10% whey concentration treatment demonstrated the greatest stability. The protein content exceeded the minimum limits established by the INEN 2395:2011 standard, thus enhancing the product's nutritional value. Viscosity showed a downward trend as the whey concentration increased, without affecting the product's consistency, while density showed no significant changes. Finally, in the sensory evaluation test, the 10% whey concentration treatment achieved the highest acceptance among the evaluators.